Post-fabrication Tethering of Molecular Gradients on Aligned Nanofibers of Functional Poly(ε-caprolactone)s - Silantyeva, Elena A. (Biomacromolecules, 2019)
Substrates with combinations of topographical and biochemical cues are highly useful for a number of fundamental biological investigations. Tethered molecular concentration gradients in particular are highly desired for a number of biomedical applications including cell migration. Herein, we report a versatile method for the fabrication of aligned nanofiber substrates with a tunable concentration gradient along the fiber direction. 4-dibenzocyclooctynol (DIBO) was used as an initiator for the ring-opening copolymerization of ε-caprolactone (εCL) and allyl-functionalized ε-caprolactone (AεPCL) which yielded a well-defined polymer with orthogonal functional handles. These materials were fabricated into aligned nanofiber substrates via touch-spinning. Fibers were modified post-spinning with a concentration gradient of fluorescently labeled dye via a light activated thiol-ene reaction through a mask. As a demonstration, the cell adhesive peptide RGD was chemically tethered to the fiber surface at a second functionalization site via strain-promoted azide-alkyne cycloaddition (SPAAC). This novel approach affords fabrication of dual functional nanofiber substrates that can be potentially used for cell migration optimization.